2006
DOI: 10.1021/la061586r
|View full text |Cite
|
Sign up to set email alerts
|

Swelling Behavior of Chitosan Hydrogels in Ionic Liquid−Water Binary Systems

Abstract: The swelling behavior of chitosan hydrogels in ionic liquid-water binary systems was studied using hydrophilic room-temperature ionic liquids (RTILs) to elucidate the swelling mechanism of chitosan hydrogels. No penetration of RTIL into a dry chitosan material was observed. Swelling was achieved by soaking in water-RTIL binary mixtures, with larger swelling observed at higher water contents. In one instance, the binary mixture was acidic and produced larger than expected swelling due to the dissociation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0
2

Year Published

2008
2008
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 36 publications
3
38
0
2
Order By: Relevance
“…We could assume that BMIMBF 4 acts as a dehydrating agent for the swollen PVA hydrogels. This behaviour does not seem to be unique, as similar phenomena have been noted and reported also for chitosan hydrogels, when in contact with BMIMBF 4 [24]. So, in case the practical interest is to load the PVA hydrogel with BMIMBF 4 , we have to use more highly diluted IL solution for the gel immersion.…”
Section: Determination Of Bmimbf 4 Mass Sorbedsupporting
confidence: 77%
See 1 more Smart Citation
“…We could assume that BMIMBF 4 acts as a dehydrating agent for the swollen PVA hydrogels. This behaviour does not seem to be unique, as similar phenomena have been noted and reported also for chitosan hydrogels, when in contact with BMIMBF 4 [24]. So, in case the practical interest is to load the PVA hydrogel with BMIMBF 4 , we have to use more highly diluted IL solution for the gel immersion.…”
Section: Determination Of Bmimbf 4 Mass Sorbedsupporting
confidence: 77%
“…[11,12,33,34]. The behaviour of hydrogels with different compositions, in the presence of different ionic substances has been studied [13,18,[23][24][25]32]. PVA is a widely used polymer, due to its exceptional properties such as non-toxicity, non-carcinogenity, water solubility, biodegradability, biocompatibility, good mechanical and optical properties that could generate hydrogels by physical and chemical ways.…”
Section: Introductionmentioning
confidence: 99%
“…We have found that room-temperature hydrophilic ionic liquids (RTILs) can produce suitable conditions. The feasibility of using RTILs was suggested by our previous work, [14] which showed that 100 % of RTILs will absorb water even when bound to a polymer network. Moreover, some RTILs can create low-pH conditions when in contact with water, and such acidic conditions have been used to promote coagulation in the wet spinning of DNA fibers.…”
mentioning
confidence: 99%
“…This is because some of the PEI/PAA may have swelled and partly peeled off, due to the b-CD-IL assembly process. [30][31][32] It was clear that although the b-CD-IL can be assembled on to the PEI/PAA due to the electrostatic adsorption force, the b-CD-IL will, to Figure 7. UV-vis spectra of (PAA/IL) n films with n 5 1-6 on quartz substrates.…”
Section: Morphologies Of B-cd-il/paa Membranesmentioning
confidence: 99%